The Method of Evangelizing Jesus - Ongki Tani'i; Mangadar Simbolon (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
Humans have fallen into a slump of sin resulting in extraordinary effects in various aspects so that happiness and prosperity are difficult to obtain. If sin is allowed to continue to run rampant then all humans will perish as a result of sin. God provides a solution to get out of sin, which is to come to Jesus Christ. The problem is that not everyone is aware of their sinfulness which leads to destruction, for this reason evangelism is needed to win their souls to salvation. And the best method of evangelism is the method practiced by Jesus Christ. The purpose of this research is for every follower of Jesus to understand his responsibility for the mission of salvation and know a good method of evangelism, by reconstructing the evangelism method in John 4:1-42 based on what Ellen White wrote about Jesus' evangelism method. This research method uses qualitative methods through a review of literature studies. Evangelism is the Great Commission that Jesus conveyed to His disciples and people before ascending to heaven. Evangelism is the responsibility of every Christian, to bring everyone to Christ. Evangelism is the mission of salvation that Jesus declared to lead people to receive His grace.